'The Other End of a Trajectory': Operation Backfire and the German Origins of Britain's Ballistic Missile Programme. Issue 6 (1st November 2020) - Hall, Charlie
Abstract: The ballistic missile age dawned in September 1944, when Nazi Germany began its V-2 campaign against Britain and Western Europe. One year later, in October 1945, the British launched a V-2 rocket themselves, as the culmination of Operation Backfire. This article will chart Britain's development of a guided missile capacity in the years immediately following the Second World War, and the importance of German expertise therein. It will also explore how this transnational process occurred within a broader international context, especially the reconfiguration of the Anglo-American relationship and the growing threat of the Soviet Union. As such it will show how swiftly the Cold War arms race emerged from the ashes of the previous conflict, how technology and international relations are intimately entwined, and how Britain was an active and enthusiastic participant in the very earliest days of the missile age.